Editorial Note (American Journal of Islam and Society, 2023)
In this issue, you will find three peer-reviewed articles and two forum essays. Adrien A. P. Chauvet’s “Cosmographical readings of the Qurʾan” is a trained physicist’s probing, multidisciplinary inquiry about a topic of great interest to the recent generations of Muslims about the compatibility of Islam and science, and about the obvious exuberance Muslims feel when some modern discoveries point to the Qurʾanic truth. As a trained physicist, he wonders whether and how we can be sure that the scientific paradigms endorsed today will endure, and therefore, more pertinently, “how can the text stay scientifically relevant across the ages, while science itself is evolving?” It thus advances the scholarship on the scriptures’ relevance to past and present scientific paradigms, reviewing multiple ancient cosmographical paradigms (Egyptian, Mesopotamian, Hebraic, Greek, Christian, Zoroastrian and Manichean) as well as modern ones, while being grounded in Islamic theology and philosophy of science. It manages to advance a novel thesis in the growing field of Islam and science, advocating for a multiplicity of correspondences between both past and modern scientific paradigms, even if these paradigms conflictwith one another.